Wrangling Shape-Shifting Morpheeins to Tackle Disease and Approach Drug Discovery - Jaffe, Eileen K. (Frontiers in Molecular Biosciences, 2020)
Homo-multimeric proteins that can come apart, change shape, and reassemble differently with functional consequences have been called morpheeins and/or transformers; these provide a largely unexplored context for understanding disease and developing allosteric therapeutics. This article describes such proteins within the context of protein structure dynamics, provides one detailed example related to an inborn error of metabolism and potential herbicide development, and describes the context for applying these ideas for understanding disease and designing bioactive molecules, such as therapeutics.